High prevalence and genetic diversity of Treponema paraluisleporidarum isolates in European lagomorphs - Sascha Knauf; Linda Hisgen; Erik O. Ågren; Alexander M. Barlow; Marcus Faehndrich; Ulrich Voigt; Luisa Fischer; Linda Grillová; Luisa K. Hallmaier-Wacker; Marja J. L. Kik; Jana C. Klink; Jitka Křenová; et al. (Microbiology Spectrum, 2024)
ABSTRACT The bacterium Treponema paraluisleporidarum causes syphilis in lagomorphs. In a set of 1,095 samples from four species—European brown hare, mountain hare, Corsican hare, and European rabbit—we tested for infection and genotyped the strains that infect wild lagomorphs. Samples originate from Sweden, the Netherlands, the United Kingdom, Germany, the Czech Republic, and Italy. The phylogenetic analyses of two informative gene targets (tp0488 and tp0548) showed high genetic diversity among the lagomorph-infecting treponemes. More specifically, we found a high number of nucleotide variants and various short repeat units in the tp0548 locus that have not been described for human syphilis and primate yaws causing Treponema pallidum. While the functional aspect of these short repeat units remains subject to ongoing investigations, it likely enables the pathogen to better survive in its lagomorph host. Our data did not support any geographic clustering, which is equally reflected in the host population genetics as shown by mitochondrial genome data corresponding to the sampled lagomorph populations. This is unexpected and in contrast with what has been shown for nonhuman primate infection with T. pallidum. In the future, the combination of multi-locus sequence typing and whole genome data from modern and ancient samples from a wide geographic range and multiple lagomorph species will contribute to a better understanding of the epidemiology and evolutionary path of lagomorph-infecting treponemes. In conclusion, our current study demonstrates widespread infection and a high genetic variation of the syphilis-causing pathogen in a higher number of positively PCR-tested European lagomorphs (n = 302/1,095). IMPORTANCE Syphilis is an ancient disease of humans and lagomorphs caused by two distinct but genetically closely related bacteria (>98% sequence identity based on the whole genome) of the genus Treponema. While human syphilis is well studied, little is known about the disease in the lagomorph host. Yet, comparative studies are needed to understand mechanisms in host–pathogen coevolution in treponematoses. Importantly, Treponema paraluisleporidarum–infected hare populations provide ample opportunity to study the syphilis-causing pathogen in a naturally infected model population without antibiotic treatment, data that cannot be obtained from syphilis infection in humans. We provide data on genetic diversity and are able to highlight various types of repetitions in one of the two hypervariable regions at the tp0548 locus that have not been described in the human syphilis-causing sister bacterium Treponema pallidum subsp. pallidum.